Eficácia da avaliação de desempenho em IFES: percepções de servidores técnico-administrativos e gestores em uma unidade acadêmica da Universidade Federal do Ceará - Rocha, Cristiane Sampaio (2023)
Performance evaluation, which in the public sphere is the representation of the principle of efficiency – introduced by the Administrative Reform through Constitutional Amendment nº 19/98 – seeks the institution's growth through the development of its human resources. Guided by objective criteria, it is expected that both sides involved, evaluators and evaluated, assume the same commitment and responsibility in the process, with no room for subjectivity. The objective of this study is to analyze the perception of technical-administrative servants and managers, of an academic unit, of the Federal University of Ceará, about the effectiveness of the performance evaluation. The research is of an applied nature, of the descriptive type, with a qualitative approach. This is a field survey. For the collection of information, a mixed questionnaire was applied, aimed at 16 technical-administrative servants and seven managers of the Federal University of Ceará. Data were entered into the ATLAS.ti 8 program, which is a technological tool for qualitative data analysis, for appreciation through the “Content Analysis” approach developed by Laurence Bardin (2016). As main results, the absence of scores in the conversion matrix for phases C and D of the process stands out, which leads to the absence of the necessary feedback. It is also noteworthy that both technical-administrative servers and managers recognize the importance of evaluation as a management tool capable of indicating a diagnosis of strengths and weaknesses, however, they demonstrate disbelief in the process, in the instrument and in the results. In relation to the actions programmed and executed after the results of the performance evaluation with a view to improving performance, it was evidenced that the majority of the administrative technicians never participated in training actions by indication of the superior, as a result of a performance demand. This time, it is concluded that, in the perception of servers and managers, performance evaluation is the instrument capable of illuminating reflections on behavior change, in the search for improving the institution's efficiency and server satisfaction, however, it is not effective, from the moment it does not reach its main objective, which is the development of the server.